Framing Gender dalam Politik Digital: Representasi Kepemimpinan Sherly Tjoanda dalam Pemberitaan dan Platform Sosial - Dhiya Fathiyyatul Aulia; Adelia Rismayani; Ika Arinia Indriyany (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2026)
The representation of women in political leadership in Indonesia remains relatively limited, particularly in executive positions at the regional level. This condition reflects structural, cultural, and symbolic barriers that influence women's participation in politics. The election of Sherly Tjoanda as the Governor of North Maluku in the 2024 regional election provides an important case for examining how female leadership is represented in the digital media space. This study aims to analyze how online media frame Sherly Tjoanda’s leadership and how gender narratives are constructed within digital political communication. This research employs a descriptive qualitative method with a case study approach and uses Robert M. Entman’s framing theory as the analytical framework, which includes define problems, diagnose causes, make moral judgement, and treatment recommendation. The research data were obtained from online media coverage and the dynamics of digital discussions throughout 2024. The findings show that media coverage does not merely convey information about Sherly Tjoanda’s political activities but also constructs layered narratives that combine the image of inspirational female leadership with expectations that remain influenced by gender stereotypes. Digital media, on one hand, provides opportunities for female politicians to build their political image, while on the other hand it can also become a space where gender bias is reproduced within public discourse. This study highlights the important role of media framing in shaping public perceptions of women’s political leadership in Indonesia’s digital political landscape.